Three dimensions for understanding communicational mediations of consumption in contemporaneity - Perez, Clotilde; Trindade, Eneus (MATRIZes, 2019)
This study aims to update a theoretical-methodological reflection on communication to address consumption phenomena and their relevance to communication studies. Our starting point is the communication aspects of sign mediation in consumption. Based on Peirce’s semiotic, we situate these phenomena in three dimensions: esthetics, ethics and logic. We focus on the socio-cultural contexts of these phenomena. Consumption is thus seen as a communicational mediation articulating aspects of socio-cultural dynamics, based on a map of mediations. This model is discussed in its intermedialities by addressing the interactions of goods and consumers which for building cultural meaning linkages.